INVENTORY OF MEDICINAL PLANT IN CAMPUS B UNIVERSITAS NEGERI JAKARTA - Handayani, Mira Wisda; Putri, Trisna Rahma; Suryanda, Ade (Universitas Pattimura, 2021)
Research on the inventory of medicinal plants at Jakarta State University Campus B was conducted from May to June 2020 at Universitas Negeri Jakarta Campus B, which is located on Jalan. Youth No.10, Rawamangun, Jakarta Timur. This study aims to determine the types of medicinal plants at Campus B. The parts of the plants used as medicine, and the types of diseases that can be treated. Research using descriptive method and literature study method. The results of the study were based on the data obtained that medicinal plants in Campus B, Jakarta State University consisted of 17 types of medicinal plants consisting of 17 families.